PENGARUH PROFESIONALISME DAN MEDIA PENDIDIKAN TERHADAP HASIL BELAJAR SISWA KELAS X DI SMA NEGERI 11 KOTA JAMBI - Putriadi, Oktavia Dwi; Indriana, Risma; Azwari, Putri Anadia (Universitas Batanghari Jambi, 2024)
This research aims to determine the influence of professionalism and educational media together on student learning outcomes at SMA Negeri 11 Jambi City. The research method used in this research is a quantitative method using multiple linear regression analysis techniques. The results of the research show that professional teachers and educational media have a positive influence on the learning outcomes of Class X students at SMA Negeri 11 Jambi City.